Prevalence rates of G6PD deficiency and factors associated with malaria preventive behaviors among primary school children in border patrol police schools, Maehongson province - Khantikul, Nardlada; Saejeng, Aungkana; Srithep, Sarinee; Ruanthip, Thunyapan; Booncomma, Somchart; Imwong, Mallika (Disease Control Journal, 2021)
G6PD deficiency may trigger hemolytic crisis after receiving treatment with some malaria drugs. This cross-sectional descriptive study aimed to investigate the prevalence of Glucose-6-Phosphate Dehydrogenase (G6PD) deficiency and determinants affecting malaria preventive behaviors of the primary school children in the border patrol police schools in Mae Hong Son province. The samples were recruited 392 students aged between 7-13 years from 11 schools in high-risk malaria territory. Data were collected by an interview with a structure questionnaire and a modified fluorescent spot test set for screening G6PD deficiency (in house method). The data analyses were to compute G6PD prevalence rates and their relationships of the determinants by displaying values of means, SD, 2test, and Multiple Logistic Regression. Findings showed the prevalence rate of G6PD deficiency of all children was 10.46 where the rate of male was significantly higher than that of female students, 13.54% vs 7.50%. It was necessitated to correct for their better knowledge of G6PD, knowledge of malaria, malaria perception and preventive behaviors within the rates of 95.15, 87.76, 55.61 and 80.87%, respectively. Associations between the determinants of preventive behaviors were significantly correlated with malaria risk perception, benefit of drugs for treatment, preventive methods, overall malaria perception, and self-care in normal life (p<0.05). Multiple Logistic Regression could predict malaria preventive behaviors that associated with perception of treatment benefits and prevention at 80.87% (adjusted odds ratio [OR]: 3.07, 95% confidence interval [CI]: 1.69-5.56, Pseudo R2=80.87). An avoidance of exposure with chemicals and malaria drugs treatment is necessary. It is needed for giving educational programs to the school children to increase perception and their participation of disease prevention.